Estrus Behaviour and Estrus Intensity Score in Relation to Hormonal Profile in Kankrej Cows at an Organized Farm - Madhavatar, Mahesh P.; Ankuya, Kanubhai J.; Pawar, Mahesh M.; Patel, Mayank P.; Srivastava, Amitkumar K.; Modi, Rakesh J. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present investigation was undertaken to study the estrus behaviour in Kankrej cattle at an organized farm during 3 different seasons. In each of three seasons, seven (07) Kankrej heifers and seven (07) Kankrej cows showing estrus were considered. In Kankrej cattle, majority of the animals showed acceptance of teaser bull (100%), estrual mucus discharge (88.10%), homosexuality (78.57%), excitement, and edema erythema and wetness of vulva (76.19% each), frequent micturition (59.52%) and bellowing (16.67%). None of the Kankrej cattle went partial or complete off-feed during estrus phase. Overall it was revealed that the estrus signs were manifested more during summer season than monsoon and winter, which shows the heat tolerance capability of the Kankrej cows in the area. Nearly three forth (73.81%) of the total Kankrej cows exhibited normal and above normal estrus intensity score, whereas one forth (26.19%) animals showed weak estrus intensity score. The difference between Kankrej cows and heifers for overall intensity score was found non-significant (p>0.05). The serum estradiol concentrations in Kankrej heifers and cows were significantly higher on the day of estrus than the corresponding levels on 11th day of estrus with inverse trend of serum progesterone in all three seasons. On the day of estrus the mean estradiol level in Kankrej heifers and progesterone levels in cows were higher in summer than winter and monsoon.